Métodos químicos para obtener varistores basados en SnO2 - Mosquera, A.; Varela, José Arana [UNESP]; Rodríguez-Páez, J. E. (Elsevier, 2006)
Synthesis of SnO2 ceramic powders was made by coprecipitation method and polymeric precursor method (Pechini) to obtain Sn-Co-Nb-Ti-Al varistor systems. The particles of the obtained ceramic powder presented nanometric size and SnO2 was the principal crystalline phase in them according to X-ray diffraction results. To determine the behavior of the synthesized samples in front of the thermal treatments, thermal analysis (DTA/TG) were made. Dilatometric studies on previously pressed samples were carried out. The optimal conditions of sintering of this raw material were determined. Microstructures and electric properties of sintered samples were studied using scanning electron microscopy (SEM) and I-V characteristics curves. The samples presented varistor behavior independent of the synthesis method used, with high nonlinearity values as 32. The presence of Al3+ favored the concentration of oxygen vacancies, and the grain growth.
Chemical methods to obtain SnO2 based varistors
Keywords: Coprecipitation; Pechini; SnO2; Synthesis; Varistor